Factors influencing the efficacy of invisalign in molar distalization and tooth movement - Chen, Xiaowen; Shi, Ying; Yuan, Jieying; Li, Ye; Chen, Weican (Frontiers in Bioengineering and Biotechnology, 2023)
The work aims to establish and analyze the factors influencing the efficacy of Invisalign in molar distalization and tooth movement. Objectives of the study: a) identify factors contributing to molar distalization and tooth movement; b) analyze the effectiveness of Invisalign technology in molar distalization and tooth movement. The study was conducted in 2020-2022 in Baoding (PRC) based on Baoding's first central hospital. Forty patients (mean age 28.5 ± 1.5 years, 18 to 35 years; 20 women and 20 men) participated in the study. All patients had mild to moderate degrees of tooth crowding, with an angle class II malocclusion, as well as maxillary third molars. Before and after the therapy, the condition of the alveolar bone, soft tissues, and facial height were measured. Fixation of the anterior teeth was performed. Calculations of the distal molar movement were performed. For orthodontic procedures, the second molars of the upper jaw were moved, and then the first molars were moved. Distalization of the upper molars was found to be an effective movement, with an efficiency of about 83% when vertical rectangular attachments were used. The first molar was moved distally by 2.85 mm without significant tilt or movement in the vertical plane.